IMPRESS Marathon 1.0 in Perak A Fusion of Learning, Cultural Enrichment, and Community Service - Ibrahim Ismail, Ahmad; Amy Zulaikha, Mohd Ali (UMPSA, 2024)
From 17 to 19 May 2024, a diverse group of 28 students, including 18 committee members and ten selected first-year students from the Faculty of Industrial Management (FIM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) embarked on the inaugural IMPRESS Marathon 1.0 in Perak.